A review of cost-effective black silicon fabrication techniques and applications. Issue 10 (20th February 2023) - Soueiti, Jimmy; Sarieddine, Rim; Kadiri, Hind; Alhussein, Akram; Lerondel, Gilles; Habchi, Roland
Abstract : Ever since the discovery of black silicon, scientists have been trying to come up with novel methods of utilizing this material in a variety of different industries due to its low reflectivity and excellent electronic and optoelectronic properties. Abstract : Ever since the discovery of black silicon, scientists around the world have been trying to come up with novel, cost-effective methods of utilizing this super material in a variety of different industries due to its remarkably low reflectivity and excellent electronic and optoelectronic properties. In this review, many of the most common methods of black silicon fabrication are exhibited, including metal-assisted chemical etching, reactive ion etching, and femto-second laser irradiation. Different nanostructured silicon surfaces are assessed based on their reflectivity and applicable properties in both the visible wavelength range and the infrared range. The most cost efficient technique for the mass production of black silicon is discussed, as well as some promising contender materials ready to replace silicon. Also, solar cell, IR photo-detector, and antibacterial applications are looked into, along with their respective challenges to date.